An Analysis of Idioms in “Guardian of the Galaxy Vol.2” Movie - Rosalia, Sasa; Noerazizah, Siti; Anggraeni, Anita (IKIP Siliwangi, 2018)
The aims of this research is to find out the types of idiom which is used in Guardian of Galaxy Vol.2 Movie and type of idiom which mostly presented in the movie. In this research, the writer used qualitative method. In collecting data, the writer used a movie script which downloaded from the internet and the writer analyzed it based on O’Dell & McCarthy theory. O’Dell & McCarthy argued that idioms are divided into 6 types; simile, binomials, proverbs, euphemism, clichès and fixed statement, and other language. The result of the analyzed data showed that from 6 types of idiom, only three types of idioms appear in this movie, which are; simile (4), binomial (6), and fixed statement (9). Keyword: Idiom, Movie